BaF2 Ridge Waveguide Operating at Mid-Infrared Wavelength - Cheng, Yazhou; Zhang, Xinbin; Song, Hongxiao (Frontiers in Physics, 2021)
We report on the fabrication of optical ridge waveguide in barium fluoride (BaF2) crystal by 15 MeV C5+ ions irradiation with femtosecond laser ablation. The near-field modal profile and propagation loss of the waveguide at mid-infrared wavelength 4 µm are investigated by using end-face coupling system. We implement a series of annealing treatment and it efficiently reduces the propagation loss of the waveguide. The confocal Raman spectra demonstrate that the lattice structure of BaF2 crystal does not change largely after C5+ ion irradiation.